2020
DOI: 10.3390/ijms21062177
|View full text |Cite
|
Sign up to set email alerts
|

Expression Analyses of Soybean VOZ Transcription Factors and the Role of GmVOZ1G in Drought and Salt Stress Tolerance

Abstract: Vascular plant one-zinc-finger (VOZ) transcription factor, a plant specific one-zinc-finger-type transcriptional activator, is involved in regulating numerous biological processes such as floral induction and development, defense against pathogens, and response to multiple types of abiotic stress. Six VOZ transcription factor-encoding genes (GmVOZs) have been reported to exist in the soybean (Glycine max) genome. In spite of this, little information is currently available regarding GmVOZs. In this study, GmVOZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 65 publications
1
25
0
Order By: Relevance
“…Ours is the first study to investigate the evolutionary relationships, gene duplication and selection pressure on GmVOZs and GsVOZs . Recent advancement in soybean genome sequencing made it possible to conduct present exploration [ 1 , 17 ]. This study will be helpful in laying a foundation for further work.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Ours is the first study to investigate the evolutionary relationships, gene duplication and selection pressure on GmVOZs and GsVOZs . Recent advancement in soybean genome sequencing made it possible to conduct present exploration [ 1 , 17 ]. This study will be helpful in laying a foundation for further work.…”
Section: Discussionmentioning
confidence: 99%
“…During salt stress, VOZ also response likewise in low temperature and water stress conditions. According to some reportsthe genes, responsible for salt stress tolerance, are being controlled directly or indirectly by VOZ1/2 [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the saline treatment, the seedlings were removed from the pots and held with the foam floats in the 100 mM NaCl solution. For the dehydration treatment, the seedlings were removed from the pots and left in the air at room temperature (22 °C) under water-limiting conditions to impose dehydration stress [ 39 , 56 ]. Samplings were focused on the leaf, stem and root tissues (weighed about 0.1 g of the tissues) after 0, 1, 6, 12 and 24 h after the abiotic stress treatments.…”
Section: Methodsmentioning
confidence: 99%
“…Very recently, Li et al (2020) found the role of GmVOZ1G in regulating responses to salt stress in soybean ( Glycine max ) roots. Overexpression of GmVOZ1G positively regulated salinity genes responsible for combating salt stress.…”
Section: Plasma Membrane Protein 3 (Pmp3)mentioning
confidence: 99%